Comparative Leaf Anatomy and Micromorphology of Thunbergia erecta (Benth.) T. Anderson and Thunbergia laurifolia Lindl. in Peninsular Malaysia - Siti Maisarah Zakaria; Che Nurul Aini Che Amri; Noraini Talip; Amirul Aiman Ahmad Juhari; Mohamad Ruzi Abdul Rahman; Ahmad Fitri Zohari; Mohd Norfaizal Ghazalli; Nordahlia Abdullah Siam; Rozilawati Shahari (Tropical Life Sciences Research, 2022)
Comparative leaf anatomy and micromorphology study was carried out on two selected species from the genus Thunbergia Retz. of Acanthaceae subfamily Thunbergioideae. These two investigated species were T. erecta and T. laurifolia from Peninsular Malaysia. The leaf anatomical study involve several methods such as cross-section using sliding microtome on the petioles, midribs, lamina and marginal, leaf epidermal peeling, leaf clearing and observation under a light microscope. The leaf micromorphology method involve the observation under a scanning electron microscope (SEM). This study aimed to investigate the taxonomic value of leaf anatomy and micromorphology characteristics of genus Thunbergia. The results have shown that there were five common characteristics present in both species studied and several variable characters that might be useful for species differentiation of T. erecta and T. laurifolia. The five common characteristics recorded were the presence of raphide, sinuous anticlinal walls, diacytic stomata, majority opened and minority closed venation in lamina and the presence of peltate glandular (unicellular terminal) trichome. The variable characteristics included were petiole, and marginal outlines, types of vascular bundles, the presence of druse, marginal venation, stomata occurrence, types of wax, cuticular sculpturing and types of trichomes. In conclusion, findings in this study showed that leaf anatomical and micromorphological characteristics possessed taxonomic value that can be used in the species identification for the genus Thunbergia specifically for T. erecta and T. laurifolia. Kajian perbandingan ciri anatomi dan mikromorfologi daun telah dijalankan ke atas dua spesies terpilih dalam genus Thunbergia Retz. (Acanthaceae) subfamili Thunbergioideae. Dua spesies yang telah dikaji ialah T. erecta dan T. laurifolia dari Semenanjung Malaysia. Kajian anatomi daun ini melibatkan beberapa kaedah seperti kaedah hirisan dengan mikrotom gelongsor pada bahagian petiol, tulang daun, lamina dan tepi daun, kaedah siasatan epidermis, kaedah penjernihan dan cerapan di bawah mikroskop cahaya. Kajian mikromorfologi melibatkan cerapan di bawah mikroskop imbasan elektron. Kajian ini bertujuan untuk melihat nilai taksonomi ciri anatomi dan mikromorfologi daun dalam genus Thunbergia. Hasil kajian menunjukkan terdapat lima ciri sepunya ke atas spesies yang dikaji dan beberapa ciri variasi yang boleh digunakan untuk pembezaan di antara T. erecta dan T. laurifolia. Lima ciri sepunya yang telah direkodkan ialah kehadiran rafid, dinding antiklinal sinuous, stomata diasitik, peruratan lamina daun majoriti terbuka dan minoriti tertutup serta kehadiran trikom kelenjar peltat (terminal unisel). Ciri variasi termasuklah bentuk petiol dan tepi daun, jenis tisu vaskular, kehadiran drus, kehadiran stomata, peruratan tepi daun, jenis lilin, ukiran kutikel dan jenis trikom. Kesimpulannya, hasil kajian menunjukkan ciri anatomi dan mikromorfologi daun mempunyai nilai taksonomi yang boleh digunakan dalam pengecaman spesies bagi genus Thunbergia khususnya pada T. erecta dan T. laurifolia.